Introduction to business law - Beatty, Jeffrey F.; Samuelson, Susan S.; Sánchez Abril, Patricia (Cengage Learning, 2019)
Discover the business law text you'll actually enjoy reading. Time after time, students like you have commented that this is the best text they have ever read and they had no idea law could be so interesting. The student choice every time, INTRODUCTION TO BUSINESS LAW, 6E is packed with current examples and real scenarios that bring law to life for today's business student. Extremely reader-friendly, this engaging presentation uses conversational writing to explain complex topics in easy-to-understand language. Memorable real-world stories help the authors illustrate how legal concepts apply to everyday business practice. This edition emphasizes the digital landscape with new information on privacy and intellectual property. An updated ethics chapter offers a practical approach, using the latest research to explain why people make unethical decisions.